Multiple neurological effects associated with exposure to organophosphorus pesticides in man - Jokanović, Milan; Oleksak, Patrik; Kuca, Kamil (Toxicology, 2023)
This article reviews available data regarding the possible association of organophosphorus (OP) pesticides with neurological disorders such as dementia, attention deficit hyperactivity disorder, neurodevelopment, autism, cognitive development, Parkinson's disease and chronic organophosphate-induced neuropsychiatric disorder. These effects mainly develop after repeated (chronic) human exposure to low doses of OP. In addition, three well defined neurotoxic effects in humans caused by single doses of OP compounds are discussed. Those effects are the cholinergic syndrome, the intermediate syndrome and organophosphate-induced delayed polyneuropathy. Usually, the poisoning can be avoided by an improved administrative control, limited access to OP pesticides, efficient measures of personal protection and education of OP pesticide applicators and medical staff.
Keywords: Pesticides; Organophosphates; hyperkinetická porucha; Attention Deficit Disorder with Hyperactivity; lidé; neurotoxické syndromy; Neurotoxicity Syndromes; pesticidy; organofosfáty; organofosforové sloučeniny; Organophosphorus Compounds; Humans